2009
DOI: 10.1111/j.1365-2966.2009.15354.x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous MITSuMEgRCICmonitoring of S5 0716+714

Abstract: We present the results of our intra‐night optical flux monitoring observations of S5 0716+714 done simultaneously in g′, RC and IC filters. The observations were done using the Multicolor Imaging Telescopes for Survey and Monstrous Explosions instrument on the 50 cm telescope at the Okayama Astrophysical Observatory over 30 nights between 2008 March 11 and 2008 May 8. Of these 30 nights, 22 nights have continuous (without any break) observations with the duration ranging from 1 to 6 h and hence were considered… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 52 publications
2
29
0
Order By: Relevance
“…This blazar has been a target of a number of intra‐night monitoring campaigns. Practically all studies, for example Sagar, Gopal‐Krishna & Mohan (), Nesci, Massaro & Montagni (), Wu et al (), Gu et al (), Montagni et al (), Pollock, Webb & Azarnia (), Gupta et al (), Stalin et al (), Poon, Fan & Fu (), Carini, Walters & Hopper () and Rani et al (), report significant variations, which can typically be described as smooth fluctuations or a sequence of trends, often abruptly changing direction. Some reports even imply the presence of very rapid (tenths of a magnitude) changes within a few minutes (Fan et al ) and/or quasi‐periodic oscillations (Gupta, Srivastava & Wiita ; Rani et al ) on a ∼15‐min time‐scale.…”
Section: Resultsmentioning
confidence: 99%
“…This blazar has been a target of a number of intra‐night monitoring campaigns. Practically all studies, for example Sagar, Gopal‐Krishna & Mohan (), Nesci, Massaro & Montagni (), Wu et al (), Gu et al (), Montagni et al (), Pollock, Webb & Azarnia (), Gupta et al (), Stalin et al (), Poon, Fan & Fu (), Carini, Walters & Hopper () and Rani et al (), report significant variations, which can typically be described as smooth fluctuations or a sequence of trends, often abruptly changing direction. Some reports even imply the presence of very rapid (tenths of a magnitude) changes within a few minutes (Fan et al ) and/or quasi‐periodic oscillations (Gupta, Srivastava & Wiita ; Rani et al ) on a ∼15‐min time‐scale.…”
Section: Resultsmentioning
confidence: 99%
“…The redshift determinations (z ≈ 0.3) are based on measurements of the size of a marginally detected host galaxy and a location near three galaxies with redshifts of 0.26 (Bychkova et al 2006;Nilsson et al 2008). Optical variability has been studied by many teams; the blazar exhibits persistent activity on both long and short (intraday) timescales, as shown by, e.g., Wagner et al (1996), Ghisellini et al (1997), Hagen-Thorn et al (2006), and Stalin et al (2006Stalin et al ( , 2009, and by the results of several WEBT campaigns (Raiteri et al 2003;Ostorero et al 2006;Villata et al 2008;Chen et al 2008). Violent polarimetric variability of S5 0716+71, among other blazars, was studied by Ikejiri et al (2011).…”
Section: Introductionmentioning
confidence: 99%
“…Quirrenbach et al (1991) found that the blazar has a possible QPO on the timescale of ∼ 1 day. Stalin et al (2009) presented the results of intra-night optical monitoring of S5 0716+714 who gave evidences for possible quasi-periods ranging from 0.9 to 4.3 h. Gupta et al (2009) found high probabilities (from 95% to >99%) quasi-periodic IDV timescales between ∼25 and ∼ 73 minutes (min), which is the first good evidence for quasi-periodic components in the optical intra-day variable light curves of any blazars. Using several different techniques, Rani et al (2010) discovered an approximately 15 min quasi-period at a > 3σ confidence level for S5 0716+714.…”
Section: Introductionmentioning
confidence: 88%